Case Report: Telitacicept for interstitial lung disease associated with idiopathic inflammatory myopathies: an observational study - Chen, Xue; Li, Mengshan; Sun, MingFang; Xie, XinTong; Zhao, Xi; Chen, Yan; Dai, HuanZi (Frontiers in Pharmacology, 2025)
BackgroundInterstitial lung disease (ILD) is the most common complication and the major cause of mortality among patients with idiopathic inflammatory myopathies (IIMs). Currently, no recommended standard treatment for IIM-associated ILD. In this observational study, we evaluated the efficacy and safety of telitacicept in treating IIM-associated ILD.MethodsWe included 10 patients with IIM-associated ILD; of them, seven had antisynthetase syndrome-associated ILD, one had anti-MDA5 antibody-positive dermatomyositis (DM)-associated ILD, and 2 had DM-associated ILD. Four patients with severe ILD were treated with a combination of rituximab (RTX) (375 mg/m2/week for 4 weeks) and telitacicept (160 mg/week). Six patients had refractory IIM-associated ILD; of them, two received RTX (375 mg/m2/week for 4 weeks) in combination with telitacicept (160 mg/week), and four were treated with telitacicept (160 mg/week) alone because they had an increased infection risk.ResultOver the 24-week follow-up, glucocorticoid dosage was reduced to 5–10 mg/day and that of telitacicept treatment was increased to 160 mg every 2 weeks in all patients. These patients exhibited alleviation of rash, joint swelling and pain, muscle pain and weakness, and dyspnea. Compared with before treatment, the Manual Muscle Testing 8 score and PaO2/FiO2 ratio increased by 25.1% and 28.2% after treatment, respectively. Lung function also exhibited considerable improvements, with percentages of forced vital capacity and diffusing capacity of the lungs for carbon monoxide increasing by 20.4% and 30.2%, respectively. Posttreatment chest high-resolution computed tomography revealed significant improvements compared with baseline. Only one patient experienced a mild lung infection, and no further infections occurred after telitacicept dose was reduced. One patient was administered additional nintedanib for pulmonary fibrosis due to insufficient improvement in lung function.ConclusionTelitacicept demonstrates substantial clinical efficacy in the treatment of IIM-associated ILD, accompanied by a low infection rate and a favorable safety profile.